STRATEGI PENGEMBANGAN KEWIRAUSAHAAN FTI USAKTI - Teddy Siswanto; Hartini Hartini; Ratna Shofiati; Wawan Kurniawan (Universitas Trisakti, 2020)
The implementation of Entrepreneurship at FTI Trisakti University which is still ongoing for 3 years 2017- 2019. The implementation of Entrepreneurship is an Entrepreneurship Community Development Scheme Entrepreneurship Development Program supported by funding from the Ministry of Research and Technology which aims to foster independent entrepreneurship among students and alumni. It is not easy to develop entrepreneurship in a campus environment with diverse backgrounds in the families of students' families, for this reason a Mentoring method was chosen to be able to help and direct student tenants to be able to obtain the passion that exists in entrepreneurship. The results of this entrepreneurial activity resulted in 20 entrepreneurial tenants coming from alumni and students as well as entrepreneurship textbooks and industrial design intellectual property rights which are currently still in the submission process. The implication of this entrepreneurship development program is to improve semester learning plans for entrepreneurship courses in the curriculum of the study program